2015
DOI: 10.2106/jbjs.n.00073
|View full text |Cite
|
Sign up to set email alerts
|

Revision Total Hip Arthoplasty: Factors Associated with Re-Revision Surgery

Abstract: When evaluating patient, implant, and surgical factors at the time of revision total hip arthroplasty, age, surgeon experience, implant fixation, and bearing surfaces had significant impacts on the risk of re-revision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 49 publications
3
43
0
4
Order By: Relevance
“…THA after post traumatic arthritis or avascular necrosis associated with acetabular fractures, will markedly improve patients' quality of life 88,89,156 , but it is associated with a higher rate of complications, reduced long time survival 90,98,99 and less improvement on patients symptoms 157,158 compared to a primary total hip replacement. In fact, the results after secondary THA in acetabular fractures are similar to that of revision arthroplasty 159,160 . For simple minimally displaced acetabular fractures developing post traumatic OA or AVN and a subsequent need for THA this is not necessarily so.…”
Section: Secondary Total Hip Replacementmentioning
confidence: 62%
“…THA after post traumatic arthritis or avascular necrosis associated with acetabular fractures, will markedly improve patients' quality of life 88,89,156 , but it is associated with a higher rate of complications, reduced long time survival 90,98,99 and less improvement on patients symptoms 157,158 compared to a primary total hip replacement. In fact, the results after secondary THA in acetabular fractures are similar to that of revision arthroplasty 159,160 . For simple minimally displaced acetabular fractures developing post traumatic OA or AVN and a subsequent need for THA this is not necessarily so.…”
Section: Secondary Total Hip Replacementmentioning
confidence: 62%
“…Previously, Jo et al [9] reported a 22.6 % re-revision rate in 539 hips. One reason for our lower re-revision rate was that only two patients received a constrained liner; although the use of a constrained liner can restore and maintain hip stability [11,24], it also increases the risk of re-revision [25]. Another reason for this difference was the short follow-up period used in our study.…”
Section: Discussionmentioning
confidence: 90%
“…The 10-year survival rate for THA after primary OA is excellent, generally around 95% for both cemented and uncemented implants according to different arthroplasty registries [6,10]. For THA after operatively treated acetabular fractures, the long-term survival is obviously less satisfying and compare with the survival of revision arthroplasties, generally reported to be around 80% [11,14]. The relatively high number of patients needing impaction bone grafting and the fact that these hips have been operated on before contribute to this, resulting in increased rates of component loosening and other complications like dislocations and infections.…”
Section: Discussionmentioning
confidence: 99%